Extraction and GC-MS analysis of phenolic acids in rhizosphere soil of Pinellia ternate. Issue 3 (September 2022) - Meng, Lifen; Xia, Zhi; Lv, Jingsong; Liu, Gaofu; Tan, Ye; Li, Qianzhu
Abstract: In this paper, five phenolic acids in the rhizosphere soil of Pinellia ternate were determined to have strong allelopathy to Pinellia ternate . The phenolic acids in rhizosphere soil and non continuous cropping soil of Pinellia ternate for two years were extracted and detected by GC-MS, 5 phenolic acids were found to have different content changes. By comparing the contents of phenolic acids in the rhizosphere soil before, during and after planting, and combining with the literatures, it was determined that protocatechuic acid, vanillic acid, vanillin, syringate and syringaldehyde had strong allelopathy on the growth and development of Pinellia ternate . Furthermore, the effects of the above five phenolic acids on the growth of Pinellia ternate, the growth of seedlings and the comparison of tuber size were investigated. The results showed that the five phenolic acids had inhibitory effects on the growth of Pinellia ternate .